The academic's guide to publishing - Kitchin, Rob (Sage study skills., 2005)
This definitive guide to successfully publishing social science research demonstrates that completing a project is only the first phase of research. The Academics' Guide to Publishing : explains the different ways in which research can be disseminated; demonstrates how the structures, practices and procedures involved work; and situates research in the larger and changing context of Higher Education. For postgraduates or academics in the social sciences The Academics' Guide to Publishing provides essential guidance on how to secure a job, how to gain tenure, how to survive research assessment.